2017
DOI: 10.3892/ol.2017.7677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silencing colon cancer-associated transcript 2 on the proliferation, apoptosis and autophagy of gastric cancer BGC-823 cells

Abstract: The role of long non-coding RNAs (lncRNAs) in the carcinogenesis and progression of tumors has been receiving increasing attention. Colon cancer-associated transcript 2 (CCAT2), a type of oncogenic lncRNA, is regarded as a novel biomarker of poor prognosis and metastasis in various types of cancer. However, the molecular contributions of CCAT2 to gastric cancer (GC) progression remain largely unclear. The aim of the present study was to demonstrate the effect of silencing CCAT2 on the biological behavior of GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…In addition to the proliferation, a previous study has proved that the apoptotic index of BGC-823 cells is significantly increased by silencing of CCAT2. 11 In consistent with previous study, we found that siRNA-CCAT2 transfection significantly increased the percentage of apoptotic cells. In addition, siRNA-CCAT2 transfection significantly upregulated P53 and Caspase-8, and downregulated Bcl-2 in HGC-27 and SGC-7901 cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition to the proliferation, a previous study has proved that the apoptotic index of BGC-823 cells is significantly increased by silencing of CCAT2. 11 In consistent with previous study, we found that siRNA-CCAT2 transfection significantly increased the percentage of apoptotic cells. In addition, siRNA-CCAT2 transfection significantly upregulated P53 and Caspase-8, and downregulated Bcl-2 in HGC-27 and SGC-7901 cells.…”
Section: Discussionsupporting
confidence: 93%
“…This result is just consistent with previous studies that CCAT2 knockdown significantly inhibits the growth ability and survival rate of BGC-823 cells. 10,11 We also found that siRNA-CCAT2 transfection significantly inhibited the colony formation, and downregulated PCNA in HGC-27 and SGC-7901 cells. These results further illustrate that silencing of CCAT2 inhibits the proliferation of GC cells.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Among them, some lncRNAs were de ned as protective factors while others were risk factors [25,[41][42][43][44]. Furthermore, several studies have proved that lncRNAs participated in the progression, especially malignant progression of GC through regulating autophagy-related mRNAs [24][25][26][27][28][29]45].…”
Section: Discussionmentioning
confidence: 99%
“…Pieces of evidence showed that lncRNA is vital for the occurrence, prognosis, and chemoresistance of GC by regulating autophagy-related mRNA [24][25][26]. Some studies have demonstrated that silencing of LINC01419 and CCAT2 promotes autophagy through constraining the PI3K/Akt1/mTOR pathway thus inhibiting the invasion and migration of GC cells [27,28]; Another study also revealed that autophagy was associated with the proliferation of GC cells, partially due to the MALAT1 promoted by downregulating miR-204 [29]. However, most of these experiments only explored the role of one or a few lncRNAs in the autophagy of GC, and could not fully explain the relevant mechanisms.…”
Section: Introductionmentioning
confidence: 99%